Exploring the nexus of agricultural policy reforms and food security - Barel-Shaked, Sagit; Buda, Erez (Frontiers in Sustainable Food Systems, 2024)
Agricultural policies play a critical role in determining the availability and stability of food supplies for individuals and communities. This study underscores the importance of incorporating social, economic, environmental, and political dimensions of food security when developing agricultural policy reforms. The study has two main objectives: 1) to disentangle the complexity surrounding food security by mapping policy reform decisions onto a suggested framework, and 2) to provide an empirical basis for analyzing food security using frame package analysis.To achieve these objectives, this study conducted an inductive frame analysis of agricultural policy reforms, using the theoretical framework of the "fractured consensus" regarding the CAP (Common Agricultural Policy) as proposed by Candel et al. (2014). The case of Israel was chosen as an empirical example for the frame package analysis. The extended suggested theoretical framework can contribute to enhancing the research literature on the nexus between agricultural policy reforms and food security from both theoretical and empirical perspectives. Additionally, the proposed framework and its application can serve as a benchmark for evaluating agricultural policy reforms in the context of food security and developing practical strategies in the agri-food sector, considering the involvement of multiple players and interests.